Loan Loss Provisioning Pratices in Asian Financial Systems - Xie, Mingshan (2013)
As Basel II aims to increase the sensitivity of bank's capital requirements to the underlying risk of the assets, it may also introduce procyclical effects on the financial system. Specific attention has been paid to the role of bank's loan loss provisioning, which plays an essential part of the overall minimum capital regulatory framework. This paper aims to investigate the determinants of loan loss provisioning practices over a sample of 40 large Asian banks from Hong Kong, Japan, Philippines and Thailand during 2005 to 2012. It is motivated by the hypothesis that both macroeconomic and bank-specific factors have an effect on the provisions to cover risks. The results showed that instead of having procyclical loan loss provisioning practices like most OECD countries, provisions turns to be substantially higher when GDP growth is higher in Asian countries, reflecting increased riskiness of the credit portfolio when the business cycle turns upwards. In addition, there is no evidence of income-smoothing among the Asian jurisdictions except Philippines, in which earnings to assets ratio is positively correlated. The procyclical effect can be mitigated somewhat as provisions rise in times when earnings are higher, suggesting bank managers do save earnings through loan loss provisions in good times and borrow earnings using loan loss provisions in bad times.